1994
DOI: 10.1093/rheumatology/33.3.224
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cytokines on Alkaline Phosphatase and Osteocalcin Production, Calcification and Calcium Release by Human Osteoblastic Cells

Abstract: We examined the effect of TNF-alpha, IL-1 beta and IL-6 on alkaline phosphatase (ALP) and osteocalcin (OC) production, calcification and calcium (Ca) release in human osteoblastic cell cultures obtained from human periosteum. The cells were cultured with varying concentrations of cytokines for 3 days. TNF-alpha and IL-1 beta significantly inhibited ALP production, decreased cellular Ca content, and significantly enhanced 45Ca release in human osteoblastic cells. IL-6, on the other hand, significantly suppresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 0 publications
3
40
0
Order By: Relevance
“…IL-1b, TNF-a, and IFN-g have been shown to inhibit bone nodule formation, decrease ALP activity, inhibit OCN and col-I deposition, in both mouse and human osteoblasts [33,35,[59][60][61][62][63][64][65][66]. Many of these effects are mediated by NO and PGE 2 pathways, which are stimulated by these cytokines [32,67].…”
Section: Discussionmentioning
confidence: 99%
“…IL-1b, TNF-a, and IFN-g have been shown to inhibit bone nodule formation, decrease ALP activity, inhibit OCN and col-I deposition, in both mouse and human osteoblasts [33,35,[59][60][61][62][63][64][65][66]. Many of these effects are mediated by NO and PGE 2 pathways, which are stimulated by these cytokines [32,67].…”
Section: Discussionmentioning
confidence: 99%
“…ALP is an important early marker of osteoblast differentiation (Kim et al 2004, ten Dijke et al 2003 which controls the precipitation of hydroxyapatite crystals in the early phase of mineralization in bone formation process (Anderson 2003, Manolagas 2000. Moreover, Chaudhary et al (2004) have reported that the ALP activity is closely associated with the formation of mineralized matrix while OCN, BGN and COL1A2 are major proteins commonly found in extracellular bone matrix and are believed to play an important role in bone formation (Chen et al 2003, 2004, Kuroki et al 1994, Parisuthiman et al 2005, Pischon et al 2004, Regazzoni et al 2001, Sierra et al 2003, Takeuchi et al 1996, Takuwa et al 1991, Viereck et al 2002, Young et al 2002.…”
Section: Discussionmentioning
confidence: 99%
“…22,23,28,[72][73][74][75][76][77][78] Although osteoblast differentiation is important in the evaluation of bone collagen, no studies in animal models or humans with renal failure have been reported. Our results showed a decrease in Runx2, Alpl, and Spp1 mRNA expression, despite increased osteoblast number in the adenine group, and a AGEs suppress LOX in the ROD rat C Aoki et al decrease in Spp1 mRNA in AGE-BSA-treated osteoblasts.…”
Section: Discussionmentioning
confidence: 99%